Multiple‐input multiple‐output with frequency diverse array radar transmit beamforming design for low‐probability‐of‐intercept in cluttered environments - Panke Jiang; Pengcheng Gong; Yuntao Wu; Xiong Deng (IET Signal Processing)
Abstract Multiple‐input multiple‐output with frequency diverse array (FDA‐MIMO) radar has drawn great attention due to providing the range‐angle beampattern via designing the transmit beamforming matrix. In this work, the authors investigate the transmit beamforming matrix optimization for Low‐Probability‐of‐Intercept (LPI) of FDA‐MIMO radar, which can accurately control the transmit beam energy to meet the LPI requirements and the clutter suppression. The idea of the transmit beamforming matrix design is to minimise the transmit power in a specific direction and simultaneously maximise the signal‐to‐interference‐plus‐noise ratio under the power constraint on each array element. To this end, a constrained multiple‐ratio fractional programming model with concerning the transmit beam matrix and the receive filter is first constructed, and then, it is transformed into two suboptimisation problems using a circular iterative approach. Moreover, the specific solution of the transmit beamforming matrix is obtained using the quadratic transformation method and the alternating direction method of multipliers algorithm. In addition, the computational complexity is also analysed in this paper. The simulation results demonstrate the correctness and effectiveness of the proposed method.